Glucagon-Like Peptide-1 Receptor Agonists for Non-Alcoholic Fatty Liver Disease in Type 2 Diabetes: A Meta-Analysis - Wong, Chloe; Lee, Ming Hui; Yaow, Clyve Yu Leon; Chin, Yip Han; Goh, Xin Lei; Ng, Cheng Han; Lim, Amanda Yuan Ling; Muthiah, Mark Dhinesh; Khoo, Chin Meng (Frontiers in Endocrinology, 2021)
Objective: Non-alcoholic fatty liver disease is highly prevalent in patients with type 2 diabetes mellitus. Studies on glucagon-like peptide-1 receptor agonists for the treatment of non-alcoholic fatty liver disease have reported promising results. Despite this, there has been limited evidence of its efficacy in non-alcoholic fatty liver disease patients with type 2 diabetes mellitus. This meta-analysis examined existing evidence on the efficacy of glucagon-like peptide-1 receptor agonists on the management of non-alcoholic fatty liver disease in patients with type 2 diabetes mellitus. Methods: Medline, Embase and Cochrane Central Register of Controlled Trials (CENTRAL) were searched for articles discussing the efficacy of glucagon-like peptide-1 receptor agonists on non-alcoholic fatty liver disease in patients with type 2 diabetes mellitus. Values of standardized mean differences (SMD) and risk ratio (RR) were determined for continuous outcomes and dichotomous outcomes respectively. Results: 8 studies involving 1,454 patients from 5 randomized controlled trials and 3 cohort studies were included in the analysis. Our analysis found significant improvements in hepatic fat content, liver biochemistry, body composition, glucose parameters, lipid parameters, insulin sensitivity and inflammatory markers following glucagon-like peptide-1 receptor agonist treatment. Glucagon-like peptide-1 receptor agonists significantly decreased hepatic fat content compared to metformin and insulin-based therapies. Glucagon-like peptide-1 receptor agonists also improved fibrosis markers, but this did not reach statistical significance. Conclusion: With a high prevalence of obesity and non-alcoholic fatty liver disease among patients with type 2 diabetes mellitus, glucagon-like peptide-1 receptor agonist therapy shows promise in improving both diabetes and non-alcoholic fatty liver disease phenotype.